In-flight Catering Service and Food Safety: Implementation of Hazard Analysis and Critical Control Point System in PT Aerofood ACS Surabaya - Ayu Diah Mutiara Kharisma (Universitas Airlangga, 2019)
Hazard Analysis Critical Control Point (HACCP) is a system of quality assurance and food safety in preventing the emergence of problems ranging from materials, processes, and products. HACCP is a form of risk management system that is developed to ensure food safety with a preventive approach. This system is adopted to provide food safety assurance in food production process for consumers. The in-flight catering company service observed in this study is PT. Aerofood ACS Surabaya. The implementation of HACCP system in every production process has been applied by this company. However, there is still limited study to explore the implementation of the system in the company and identify any potential impediment of the system. This research is descriptive with observation method on production process of chicken oyster sauce menu. The control points used in the process of chicken oyster sauce production is by controlling the temperature upon receiving raw materials, storage system, cooking process, blast chilling, until portioning. One out of the ten of HACCP implementation stages, monitoring activity was found has not met SNI 01-4852-1998 requirement standard. Monitoring process was not implemented while checking the core temperature of the food during the cooking process. Nine other of HACCP implementations stages including of HACCP team formation, product description, drafting flow chart, hazard identification, critical conrol point determination, critical boundary determination, correction action, verification, and documentation were already in accordance with SNI requirement standard.